ROMANS 1:3-4: AN EXAMINATION OF ITS PRIMITIVE CHARACTER - Craine, Patrick (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2023)
In his salutation in Romans, Paul inserts two verses, 1:3-4, explaining the message of the gospel with unusual expressions. The meaning of this passage has been hotly debated for centuries. In 1976, biblical scholar Martin Hengel wrote that “in recent years, more has been written about this text than about any other New Testament text.” A crucial point of the debate has been the origin of the verses, namely: To what extent is Rom. 1:3-4 from a pre-Pauline tradition? In this paper, we examine the evidence that Paul draws on an existing creedal formula and propose a hypothesis for delineating the pre-Pauline and Pauline material. As we proceed, we seek to discern what our analysis might reveal about how Christians’ understanding of their faith developed in the earliest decades of Christianity.